PENGARUH INDEPENDENSI, PENGALAMAN, OBJEKTIVITAS DAN KOMPETENSI TERHADAPKUALITAS AUDIT DENGAN ETIKA AUDITORSEBAGAI VARIABEL MODERASI(Studi Pada KAP di Semarang) - Anis Maghfiroh, 14.05.52.0157; Setyowati, Widhy (Students Journal of Accounting and Banking, 2018)
Audit quality is the quality of the work of an auditor who is shown with a reliable report of the results of the examination. Audit quality is influenced by various factors such as independence, experience, objectivity, competence and auditor ethics. This study aims to examine the influence of independence, experience, objectivity and competence on audit quality with auditor ethics as a moderation variable. The population in this study are all auditors who work in Public Accounting Firm in Semarang. Sampling was done by using purposive sampling method and obtained a sample of 81 respondents. The method of collecting primary data was conducted through survey method using questionnaire. The data obtained were analyzed using multiple linear regression model and using residual test to test the effect of moderation variable by SPSS 24.0. The results of this study show that independence, experience and competence have a positive and significant impact on audit quality while objectivity has positive and insignificant effect on audit quality. The ethics of the auditor does not moderate the influence of independence, experience, objectivity and competence on audit qualityKeywords: independence, experience, objectivity, competence, auditor ethics and audit quality